Characterization of the fish farming activity in the municipality of Leticia in the department of Amazonas - Colombia - González Villa, Angela Andrea
Fish farming is considered one of the agricultural activities with the greatest commercial projection worldwide. The municipality of Leticia is no stranger to this possibility of agricultural development. There is a fish farming activity that was characterized within the framework of the SENNOVA project: “Pilot model for the management, reproduction and commercialization of ornamental and consumption fish at the family level in the department of Amazonas”, carried out in the year 2021. For this, visits were made to the fish farmers present on the Leticia Tarapacá highway in the municipality of Leticia, in which information was collected for its characterization in four aspects: social, environmental, production and socioeconomic parameters with the use of semi-structured interviews. The results characterized 128 fish production systems. Having as main results: 1. There are two types of producers: those from indigenous communities and those from private properties. 2. There are high dependencies on the Amazon River to obtain fingerlings; 3. There are high dependencies on the concentrated food trade from Brazil and 4. Fish producers do not make economic balances between investment and profit.